Therapeutic Potential of Muli Banana Peel Extract on Modulating Inflammation, Proliferation, and Apoptosis in A Rat Model of Endometriosis - Maesaroh, Siti; Soetrisno, Soetrisno; Sentono, Harijono Kario; Indarto, Dono (Trends in Sciences, 2025)
Endometriosis is a condition characterized by the growth of tissue resembling the endometrium outside the uterine cavity, which can lead to inflammation, pelvic pain, and infertility. Muli Banana Peel Extract (MBPE) derived from Musa acuminata Colla has demonstrated therapeutic potential in the management of endometriosis. The study aims to establish MBPE as a natural therapeutic agent for endometriosis by targeting inflammation (TNFα), cell proliferation (Ki-67, BCL2), and apoptosis (Caspase 3), while also assessing its impact on lesion regression. An experimental laboratory study with a pre-posttest-only control group design for the TNFα parameter and a posttest-only control group design for other parameters was conducted using 48 Wistar rats with an autologous endometriosis model. The rats were randomly divided into 6 treatment groups (n = 8 per group). Changes in serum TNFα levels before and after treatment, as well as tissue levels of Ki-67, BCL2, and Caspase 3 after treatment, were analyzed using enzyme-linked immunosorbent assay (ELISA). Hematoxylin and eosin (HE) staining was used to evaluate lesion size. The results showed that MBPE at a dose of 400 mg/kg body weight (BW) significantly reduced serum TNFα levels (p = 0.024), decreased tissue levels of Ki-67 (p = 0.003), and increased tissue levels of Caspase 3 (p = 0.001). Rats receiving MBPE (400 mg/kg BW) exhibited significantly smaller lesion sizes (p < 0.001) compared to the control group. In conclusion, MBPE showed promising therapeutic potential for endometriosis treatment through multi-target mechanisms, effectively reducing inflammation (TNFα), inhibiting cell proliferation (Ki-67), promoting apoptosis (Caspase 3), and significantly reducing lesion size. The lack of significant BCL2 modulation indicates that MBPE may primarily target intrinsic apoptotic pathways rather than anti-apoptotic mechanisms. HIGHLIGHTS This study constitutes the first demonstration of the efficacy of Musa paradisiaca peel extract (MBPE) as a novel natural therapeutic agent for endometriosis in an animal model. Administration of MBPE at a dose of 400 mg/kg significantly reduced endometriotic lesion size through a multi-faceted mechanism involving anti-inflammatory (TNF-α reduction), anti-proliferative (Ki-67 suppression), and pro-apoptotic (Caspase-3 activation) effects. These findings provide a robust scientific foundation for the development of MBPE as a promising alternative treatment for endometriosis. GRAPHICAL ABSTRACT